Fertilizing a Patient Engagement Ecosystem to Innovate Healthcare: Toward the First Italian Consensus Conference on Patient Engagement - Graffigna, Guendalina; Barello, Serena; Riva, Giuseppe; Savarese, Mariarosaria; Menichetti, Julia; Castelnuovo, Gianluca; Corbo, Massimo; Tzannis, Alessandra; Aglione, Antonio; Bettega, Donato; Bertoni, Anna; Bigi, Sarah; et al. (Frontiers in Psychology, 2017)
Today we observe a gap between theory and practices of patient engagement. If both scholars and health practitioners do agree on the urgency to realize patient engagement, no shared guidelines exist so far to orient clinical practice. Despite a supportive policy context, progress to achieve greater patient engagement is patchy and slow and often concentrated at the level of policy regulation without dialoguing with practitioners from the clinical field as well as patients and families. Though individual clinicians, care teams and health organizations may be interested and deeply committed to engage patients and family members in the medical course, they may lack clarity about how to achieve this goal. This contributes to a wide “system” inertia – really difficult to be overcome - and put at risk any form of innovation in this filed. As a result, patient engagement risk today to be a buzz words, rather than a real guidance for practice. To make the field clearer, we promoted an Italian Consensus Conference on Patient Engagement (ICCPE) in order to provide recommendations for the provision of effective patient engagement interventions. This document reports on the main results rising from this process. To summarize, the ICCPE advised the importance of “fertilizing a patient engagement ecosystem”: an oversimplifying approach to patient engagement promotion appears the result of a common illusion. Patient “disengagement” is a symptom that needs a more holistic and complex approach to solve its underlined causes. Main recommendations about the principles to promote a patient engagement ecosystem are provided